2013
DOI: 10.1155/2013/321908
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Some Surfactants on Drag Reduction of Crude Oil Flow

Abstract: The influence of SDBS, SLS, SLES, and SS as drag reducing agents on flow of Iraqi crude oil in pipelines was investigated in the present work. The effect of additive type, additive concentration, pipe diameter, solution flow rate, and the presence of elbows on the percentage of drag reduction (%Dr) and the amount of flow increases (%FI) was addressed. The maximum drag reduction was 55% obtained at 250 ppm SDBS surfactant flowing in straight pipes of 0.0508 m I.D. The dimensional analysis was used for grouping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Cationic surfactants are not easily biodegradable, and there are a few types of zwitterionic and nonionic surfactants that are expensive. Almost all available literature on the use of surfactants to achieve crude oil drag reduction is anionic. , …”
Section: Drag Reducing Additivesmentioning
confidence: 99%
“…Cationic surfactants are not easily biodegradable, and there are a few types of zwitterionic and nonionic surfactants that are expensive. Almost all available literature on the use of surfactants to achieve crude oil drag reduction is anionic. , …”
Section: Drag Reducing Additivesmentioning
confidence: 99%
“…The micelles run in a system for suppressing friction and rising viscosity, which can be higher than in other polymers. The new characteristics of tensioners are due to the selfrepair capacity [8].…”
Section: Pipesmentioning
confidence: 99%
“…Abdul-Hadi and Khadom [12] studied oil flow in pipeline of 0.0508 m ID with four different kinds of SLES, SLS, SDBS, and SS surfactants. They found that at 250 ppm of SDBS, 55% drag reduction was found.…”
Section: Introductionmentioning
confidence: 99%